2023
DOI: 10.1002/chem.202203462
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Supramolecular Properties of Inclusion Complexes of Anthracene‐Triptycene Nanocages with Fullerene Guests and Their Dynamic Motion as Molecular Gyroscopes

Abstract: Three derivatives of macrocyclic cage compounds consisting of diarylanthracene and triptycene units were synthesized. These nanocages formed host‐guest complexes with C60 and other fullerene guests as confirmed by 1H NMR and fluorescence spectroscopy. The association constant of the mesityl and 2,4,6‐tributoxyphenyl derivatives with C60 was determined to be 2.2 × 104 L mol−1, which was larger than that of the pentafluorophenyl derivative. Direct experimental evidence of the complexation was obtained by X‐ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…Toyota et al expanded the molecular design to include the synthesis of bicyclic cage-like macrocycles composed of anthracene components. [44,45] Notably, they synthesized a series of anthracene-based nanocages that featured various electron donating or accepting substituents (13 a, 13 b, 13 c) and compared the K SV values of these compounds with those of C 60 or C 70 through fluorescence titration experiments (see Figure 5). The results revealed that the K SV values decreased in the following order: 13 a (( 22 (110 � 10) × 10 3 L mol À 1 for C 70 ), suggesting that the binding abilities decreased as electron-withdrawing groups were introduced.…”
Section: Host-guest Systems Using Arene Macrocyclesmentioning
confidence: 99%
“…Toyota et al expanded the molecular design to include the synthesis of bicyclic cage-like macrocycles composed of anthracene components. [44,45] Notably, they synthesized a series of anthracene-based nanocages that featured various electron donating or accepting substituents (13 a, 13 b, 13 c) and compared the K SV values of these compounds with those of C 60 or C 70 through fluorescence titration experiments (see Figure 5). The results revealed that the K SV values decreased in the following order: 13 a (( 22 (110 � 10) × 10 3 L mol À 1 for C 70 ), suggesting that the binding abilities decreased as electron-withdrawing groups were introduced.…”
Section: Host-guest Systems Using Arene Macrocyclesmentioning
confidence: 99%
“…1, a CH-p complex is predicted to be formed while the buckybowl is encapsulated as a lying orientation in which the C-H bonds of the buckybowl at the edge interact with the interior surface of CPP. It should be a Key Laboratory for Macromolecular Science of Shaanxi Province, School of noted that some host-guest complexes assembled by CH-p interactions have been successfully synthesized in very recent experiments, [16][17][18][19][20] despite CH-p interaction generally being considered a relatively weak non-covalent interaction. On the other hand, since both sumanene and corannulene can be treated as the fragments of fullerenes, the guest buckybowl is also expected to be stabilized in a standing orientation and the host-guest moieties should be assembled by the p-p interaction between the inner wall of CPP and the convex surface of buckybowls.…”
mentioning
confidence: 99%